Analisis Efektivitas Penggunaan Teknologi Dalam Proses Pembelajaran Pada Mata Pelajaran IPS Di SMP Negeri 2 Kedungwaru Tahun Ajaran 2024/2025 - Lia Wulandari; Nailariza Umami (Advances In Education Journal, 2025)
Education in the digital era demands the use of information and communication technology in the learning process. However, at SMP Negeri 2 Kedungwaru the use of android-based technology in social studies subjects is still not optimal. The purpose of this study was to determine the practice of using technology in the learning process in social studies subjects at SMP Negeri 2 Kedungwaru in the 2024/2025 academic year and to determine the effectiveness of using technology in the learning process in social studies subjects at SMP Negeri 2 Kedungwaru in the 2024/2025 academic year. The research method used was qualitative research with data collection through observation, interviews, and documentation. Data analysis using the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the effectiveness of using technology in the learning process in social studies subjects is not yet effective as a whole because there are still obstacles and efforts need to be made to overcome this.